Voltage profile and power quality improvement using multicell dynamic voltage restorer - Benamar Tahar Karim; Ahmed Allali; Houari Merabet Boulouiha; Mouloud Denai (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Multi-level converter topologies are increasingly being used in various applications due to their high power, high voltage, and low harmonic levels in the output waveforms. These converter topologies produce different output voltage levels and have a highly modular structure. This paper proposes the design of a dynamic voltage restorer (DVR) based on multilevel topology to enhance the voltage profile and improve the power quality in the network. The DVR is an effective, fast-acting device which detects voltage sags and swells in a transmission line and inject a compensating voltage through a boost transformer. A simulation study is carried out under MATLAB/Simulate to demonstrate the performance of the proposed DVR circuit. The simulation results show improved transient response and enhanced power quality in the transmission network.